PEMBELAJARAN BAHASA ARAB ANTARA HARAPAN DAN KENYATAAN - Akla Akla (Institut Agama Islam Negeri (IAIN) Metro, 2017)
This study aims to answer the research questions (1) how does the ability of Arabic teachers in implementing and developing teaching methods and strategies, (2) how does the ability of Arabic teachers in implementing and developing learning media, (3) how does language environment in the Arabic learning, (4) how does the students’ motivation in learning Arabic (5) how does the students’ mastery level in Arabic language. This study is quantitative research with survey approach. The respondents of this research were Arabic teachers at Madrasah Ibtidaiyah, Madrasah Tsanawiyah and Madrasah Aliyah, each of them consisted of 15 teachers, and the students at each level was 100. This research found that the students’ ability of Arabic language in Madrasah is not satisfying. This fact is as the impact of Arabic teachers who have not implemented the learning process optimally. Teachers have not optimized the implementation and the development both learning methods and media. In addition, the factors which trigger the non-success of students in learning Arabic language due to the unavailability of language environment which is created by teachers and responsible Madrasah as a media in learning Arabic as a second language.